IMPLEMENTATION OF FUZZY TIME SERIES CHEN FOR FORECASTING INDONESIAN OIL AND GAS IMPORTS VALUE - Damayanti, Septri; Yosmar, Siska; Afandi, Nur (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2023)
Indonesia is an importing country that frequently imports goods from abroad continuously every year. Imported goods are oil and gas and non-oil and gas. Oil and gas includes oil and gas. This oil and gas import value data is an example of time series data, where the data is obtained from data recapitulation at the Central Bureau of Statistics (BPS). Time series analysis is a method for predicting an event that will come by looking at data from the previous time. One of the newest methods of time series analysis used in this research is Fuzzy Time Series Chen method. The purpose of this research is to find out how the implementation of Fuzzy Time Series Chen method in predicting the value of Indonesian oil and gas imports and to know the results of forecasting the value of Indonesian oil and gas imports. In predicting the value of Indonesia's oil and gas imports using Fuzzy Time Series Chen method, the results of forecasting the value of Indonesia's oil and gas imports in August 2022 were US$ 3743.213 million with a MAPE value of 19.969%.